TANGGUNG JAWAB PELAKU USAHA TERKAIT KERUGIAN YANG DITIMBULKAN OLEH PENGGUNAAN AI DALAM LAYANAN KONSUMEN - I.G.N. Wira W.Wp.M.S; Luh Merry Dyanthi (Universitas Mahendradatta, 2026)
The development of Artificial Intelligence (AI) technology in the business sector has brought significant innovation, particularly in customer service through chatbots, recommendation systems, and service robots. However, AI is not a legal entity, but merely a tool programmed and controlled by businesses. Therefore, responsibility for losses arising from the use of AI remains with the business as the party that benefits from and controls the system. In consumer protection law, a business is defined as the party that produces, distributes, or provides goods or services to consumers.